Economic problems in the determination of the corporate profits, arising out of higher education grants awarded by the municipality of Nilo – Cundinamarca (2014)
Township Nilo a search of a holisticdevelopment of itspopulation, has sought to facilitateaccess to thesamehighereducationbyallocating subsidies forhighschoolgraduates of ENTITIES educationalinstitutions in theirterritoriesforthepurpose of thisensurethatthe target populationistheoneactuallyachievesequitable and not be moved bypeoplefromotherregions. Forthis he has issuedregulationscontained in agreements and decreesthat are consistentwiththeConstitution of Colombia and nationallaws and decreesfortheimplementation of thisprogramisfair and objective and achievetheexpectedgoalsbetweenthegoverned, howeverfound to difficulties in measuringthebenefitsfromthedevelopment of social programs, which are extensible program subsidies to higher